Audit of It Process Ai-02 CobIt in Academic Information System (Case Study on Several Vocational Higher education in Bandung) - SURYA, Rendra Trisyanto; KERIHI, Anthon Simon Yohanis; MURHABAN, Murhaban; HAQ, Ashanul (PT Keberlanjutan Strategis Indonesia, 2023)
The development of Information Technology (IT) allows the Academic Information System (SIAK) to become a central element in the management process of Higher Education, primarily Academic. On the other hand, the sophistication of IT in SIAK develops a variety of new risks (IT Risks) that accompany it if not managed properly. Therefore, the maturity level of SIAK management determines the performance of the academic activity process. In SIAK, the element that determines system performance is Application Software. The results of this study indicate that IT Process AI-02 (Procurement of Application Software) Vocational Higher Education in Bandung, as measured based on COBIT standards, is still at the 2.1 level. This means a part/function (management) already handles Software Procurement but is still